2016
DOI: 10.1002/2016jd024804
|View full text |Cite
|
Sign up to set email alerts
|

Sampling biases in CMIP5 decadal forecasts

Abstract: Recent studies examining the fidelity of decadal hindcast experiments from phase 5 of the Coupled Model Intercomparison Project have highlighted the need for larger ensembles of forecasts, compared to the initial five yearly spaced initializations, to help correct for model biases (drift). This study quantifies differences in the two drift estimates in sea surface temperature (SST) and SST anomaly (SSTA) predictions, between experiments initialized every 5 years and those initialized every year. The effect of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…Other sources of uncertainties might arise from the relatively small sample of both starting dates and ensemble size. For example, Choudhury et al () show that sampling biases might impact predictive skill assessment, especially at a regional scale. Similarly, a larger ensemble size would be expected to refine our estimate of model predictability (Deser et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Other sources of uncertainties might arise from the relatively small sample of both starting dates and ensemble size. For example, Choudhury et al () show that sampling biases might impact predictive skill assessment, especially at a regional scale. Similarly, a larger ensemble size would be expected to refine our estimate of model predictability (Deser et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Although there are other models available from the CMIP5 archive, only these models provide annual initializations over this period (other models only have initializations every 5 years). The issues arising from using an undersampled data set have already been well documented in the literature (e.g., Choudhury, Sharma, et al, ; García‐Serrano & Doblas‐Reyes, ; Smith et al, ). Choudhury, Sharma, et al () showed that using model data sets with 5 year spaced initializations leads to very large biases in the estimated drift over the tropical Pacific because of a spurious imprinting of the observed ENSO signal and, thus, leads to biased results even after drift correction.…”
Section: Models and Methodsmentioning
confidence: 95%
“…For anomaly initialization, models are initialized by adding the observed anomalies (relative to the observed mean state) to the model climatology (Smith et al, ). Theoretically, anomaly‐initialized models should not drift (Smith et al, ), although some drift generally still occurs (Choudhury, Sharma, et al, ; Kim et al, ), albeit substantially reduced. This is because the model may not simulate the long‐term trend correctly (Kharin et al, ) and the model's erroneous mean state can lead to dynamical imbalances that lead to biases and poor prediction skill (Boer et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the general case, the model attractor will be related to the real one by some combination of these three transformations. Figure 6 illustrates that the model bias may vary, not only with lead time, but with model state (e.g., whether or not the model is in an El Niño state; Choudhury et al, 2016) and whether the local model trend is different from the true trend (see Meehl, Teng, & Arblaster, 2014). For decadal forecasting in particular,…”
Section: Model Bias Drift and Bias Correctionmentioning
confidence: 99%